Method for manufacturing hollow silica particles, method for controlling shape of hollow silica particles, and intermediate of hollow silica particles
Patent Information
- Application Number
- KR1020250009755
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-01-22
- Publication Date
- 2026-08-11
- Estimated Expiration
- 2045-01-22
Smart Images

Figure 112025009031048-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present application relates to a method for manufacturing hollow silica particles, a method for controlling the shape of hollow silica particles, and an intermediate of hollow silica particles, and more specifically, to identifying a mechanism for shape control and to a method for manufacturing hollow silica particles, a method for controlling the shape of hollow silica particles, and an intermediate of hollow silica particles in which shape control is easy according to said mechanism. Background Technology
[0003] Silica nanoparticles having a hollow structure, i.e., hollow silica particles, are promising materials that can be used in energy, optics, and / or bio applications, but there may be limitations in their manufacturing methods to date. For example, Korean Registered Patent Publication No. 10-0950548 discloses a method for manufacturing hollow silica nanoparticles comprising: a first step of mixing magnetic nanoclusters and a silica precursor; a second step of forming a silica cell portion on the surface of the magnetic nanoclusters using the silica precursor; a third step of removing the magnetic nanoclusters within the silica cell portion; a fourth step of introducing NH2 as a surface functional group into the silica cell portion; and a fifth step of surface modifying the silica cell portion by covalently bonding a biocompatible polymer with the NH2. As another example, Korean Patent Publication No. 10-2018-0086616 discloses a method for manufacturing hollow silica particles, characterized by comprising the steps of: heating a solution mixed with a Zn precursor and an alkaline precipitating agent to produce ZnO inorganic template particles; reacting a silica precursor and a salt with the ZnO inorganic template particles to form a silica shell on the surface of the ZnO inorganic template particles to produce ZnO / silica core-shell particles; and removing the ZnO inorganic template particles from the ZnO / silica core-shell particles.
[0004] Hollow silica particles can be customized to meet the conditions required in various fields for expanded applications, but their synthesis mechanism has not been substantially elucidated to date.
[0005] Accordingly, there is a need for a method to elucidate the synthesis mechanism of hollow silica particles and to control characteristics such as particle surface roughness, particle shape, particle size, pore size, and / or particle uniformity by adjusting synthesis conditions. The problem to be solved
[0007] The technical problem that the present application aims to solve is to provide a method for manufacturing hollow silica particles, a method for controlling the shape of hollow silica particles, and an intermediate of hollow silica particles, which identify a mechanism for shape control.
[0008] Another technical problem that the present application aims to solve is to provide a method for manufacturing hollow silica particles, a method for controlling the shape of hollow silica particles, and an intermediate of hollow silica particles, wherein the shape control is easy according to the above mechanism.
[0009] The technical problems that this application aims to solve are not limited to those described above. means of solving the problem
[0011] To solve the above technical problem, the present application provides a method for manufacturing hollow silica particles.
[0012] According to one embodiment, the method for manufacturing the hollow silica particles may include the steps of: dissolving a water-soluble polymer electrolyte in a basic atmosphere and providing an aggregation source that aggregates the dissolved water-soluble polymer electrolyte to form a core in which the water-soluble polymer electrolyte is aggregated; providing a silica precursor in the basic atmosphere to form a shell containing silica on the core; and removing the core and forming hollow silica particles including the shell that surrounds the hollow formed in the region where the core was removed.
[0013] According to one embodiment, the shape of the hollow silica particles is controlled by adjusting the concentration of the silica precursor, and as the concentration of the silica precursor increases, the shape of the hollow silica particles can be controlled from a chain shape to a spherical shape.
[0014] According to one embodiment, the shape of the hollow silica particles is controlled by adjusting the concentration of the water-soluble polymer electrolyte, and as the concentration of the water-soluble polymer electrolyte increases, the shape of the hollow silica particles can be controlled from a spherical shape to a chain shape.
[0015] According to one embodiment, as the concentration of the water-soluble polymer electrolyte increases, the particle size and pore size of the aggregated water-soluble polymer electrolyte may increase, and as the concentration of the silica precursor increases, the thickness of the shell formed on the core may increase.
[0016] According to one embodiment, the core may be removed by heat treatment at a temperature above which the water-soluble polymer decomposes, or the water-soluble polymer may be removed by dissolving in water.
[0017] According to one embodiment, the basic atmosphere is formed from a basic solution, and the basic solution acts as a catalyst for the growth of the shell under the basic atmosphere, with the concentration controlled to be greater than 0.45 M and less than or equal to 1.35 M, and may include ammonia water.
[0018] According to one embodiment, the aggregation source may contain ethanol, which does not dissolve the water-soluble polymer electrolyte.
[0019] According to one embodiment, the silica precursor is controlled to a concentration greater than 35 mM and less than 236 mM and comprises at least one selected from the group comprising tetraethyl orthosilicate and tetramethyl orthosilicate, or at least one selected from the group comprising amine group-containing silica precursors comprising 3-aminopropyl triethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl methyldiethoxysilane, 3-aminopropyl methyldimethoxysilane, and amino silane, and the water-soluble polymer electrolyte is controlled to a concentration greater than 48 μM and less than 176 μM and comprises polyacrylic acid, It may include at least one selected from the group comprising polymethacrylic acid, polyvinyl alcohol, polyethylene glycol, polypropylene glycol, polyvinylpyrrolidone, and copolymers thereof.
[0021] To solve the above technical problem, the present application provides a method for controlling the shape of hollow silica particles.
[0022] According to one embodiment, the method for controlling the shape of the hollow silica particles comprises the steps of: manufacturing a core in which a water-soluble polymer electrolyte is aggregated; and providing a silica precursor to the core to form a shell on the core, wherein the hollow silica particles are controlled to a spherical shape by controlling the content to satisfy Formula 1 below.
[0023] <Equation 1>
[0024] (X - 87.5) 2 / 37.5 2 + (Y - 125) 2 / 75 2 = 1
[0025] (Here, X is the concentration of the silica precursor, and Y is the concentration of the water-soluble polymer electrolyte)
[0026] According to one embodiment, the method for controlling the shape of the hollow silica particles comprises the steps of: manufacturing a core in which a water-soluble polymer electrolyte is aggregated; and providing a silica precursor to the core to form a shell on the core, wherein the hollow silica particles are controlled to a content satisfying Formula 2 below to form a chain shape.
[0027] <Equation 2>
[0028] (X - 175) 2 / 95 2 + (Y - 20) 2 / 130 2 = 1 (where X < 175, Y > 20)
[0029] (Here, X is the concentration of the silica precursor, and Y is the concentration of the water-soluble polymer electrolyte)
[0030] According to one embodiment, the method for controlling the shape of the hollow silica particles may include controlling the hollow silica particles into a spherical shape and a chain shape by controlling the content to satisfy both Equation 1 and Equation 2.
[0032] To solve the above technical problem, the present application provides an intermediate of hollow silica particles.
[0033] According to one embodiment, the intermediate is an intermediate formed of hollow silica particles, comprising a core in which a water-soluble polymer electrolyte is aggregated, and a shell formed of a silica precursor on the core, wherein the intermediate has a spherical shape and contains an amount satisfying Formula 1 below.
[0034] <Equation 1>
[0035] (X - 87.5) 2 / 37.5 2 + (Y - 125) 2 / 75 2 = 1
[0036] (Here, X is the concentration of the silica precursor, and Y is the concentration of the water-soluble polymer electrolyte)
[0037] According to one embodiment, the intermediate is an intermediate formed of hollow silica particles, comprising a core in which a water-soluble polymer electrolyte is aggregated, and a shell formed of a silica precursor on the core, wherein the intermediate comprises an amount satisfying Formula 2 below and may have a chain shape.
[0038] <Equation 2>
[0039] (X - 175) 2 / 95 2 + (Y - 20) 2 / 130 2 = 1 (where X < 175, Y > 20)
[0040] (Here, X is the concentration of the silica precursor, and Y is the concentration of the water-soluble polymer electrolyte)
[0041] According to one embodiment, the intermediate may contain an amount satisfying both Formula 1 and Formula 2, and may have a spherical shape and a chain shape. Effects of the invention
[0043] According to an embodiment of the present application, a method for manufacturing hollow silica particles may be provided, comprising the steps of: dissolving a water-soluble polymer electrolyte in a basic atmosphere and providing a coagulation source that coagulates the dissolved water-soluble polymer electrolyte to form a core in which the water-soluble polymer electrolyte is coagulated; providing a silica precursor in the basic atmosphere to form a shell containing silica on the core; and removing the core and forming hollow silica particles comprising the shell that surrounds a hollow formed in the region where the core was removed.
[0044] According to an embodiment of the present application, the concentration of the silica precursor and the concentration of the water-soluble polymer electrolyte can be controlled to an amount satisfying Formula 1 below.
[0045] <Equation 1>
[0046] (X - 87.5) 2 / 37.5 2 + (Y - 125) 2 / 75 2 = 1
[0047] (Here, X is the concentration of the silica precursor, and Y is the concentration of the water-soluble polymer electrolyte)
[0048] Accordingly, the intermediate comprising the core and the shell, and the hollow silica particles produced from the intermediate can be controlled to have a spherical shape.
[0049] Alternatively, according to an embodiment of the present application, the concentration of the silica precursor and the concentration of the water-soluble polymer electrolyte can be controlled to an amount satisfying Formula 2 below.
[0050] <Equation 2>
[0051] (X - 175) 2 / 95 2 + (Y - 20) 2 / 130 2 = 1 (where X < 175, Y > 20)
[0052] (Here, X is the concentration of the silica precursor, and Y is the concentration of the water-soluble polymer electrolyte)
[0053] Accordingly, the intermediate comprising the core and the shell and the hollow silica particles produced from the intermediate can be controlled into a chain shape.
[0054] Alternatively, according to an embodiment of the present application, the concentration of the silica precursor and the concentration of the water-soluble polymer electrolyte can be controlled to an amount that satisfies both Formula 1 and Formula 2.
[0055] Accordingly, the intermediate comprising the core and the shell, and the hollow silica particles produced from the intermediate, can be controlled into a spherical shape and a chain shape.
[0056] In other words, according to the embodiments of the present application, a mechanism for controlling the shape of the hollow silica particles being manufactured can be identified. That is, according to the mechanism in which the hollow silica particles are manufactured in a spherical shape when the concentration of the silica precursor satisfies Equation 1, and the hollow silica particles are manufactured in a chain shape when the concentration satisfies Equation 2, the shape control of the hollow silica particles being manufactured can be easily controlled. Brief explanation of the drawing
[0058] FIG. 1 is a drawing for explaining a method for manufacturing hollow silica particles according to an embodiment of the present application. FIG. 2 is a drawing for explaining a method for manufacturing a core according to an embodiment of the present application. FIG. 3 is a drawing for explaining a shell manufacturing method according to an embodiment of the present application. FIGS. 4 and FIGS. 5 are drawings for explaining a shape control method according to an embodiment of the present application. FIG. 6 is a drawing for explaining hollow silica particles according to an embodiment of the present application. FIG. 7 is a transmission electron microscope (TEM) image taken after 5 hours have passed in the hollow silica particle manufacturing process according to Experimental Example 1-3 of the present application, after providing a silica precursor. FIG. 8 is a transmission electron microscope (TEM) image taken after 15 hours of providing a silica precursor in the hollow silica particle manufacturing process according to Experimental Example 1-3 of the present application. FIG. 9 is a transmission electron microscope (TEM) image of an intermediate after cleaning, prepared according to the hollow silica particle manufacturing process of Experimental Example 1-3 of the present application. FIG. 10 is a diagram showing the shape of hollow silica particles according to Experimental Examples 1-1 to 1-7 according to the concentration of the water-soluble polymer electrolyte and silica precursor of the present application. FIG. 11 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 1-1 of the present application. FIG. 12 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 1-2 of the present application. FIG. 13 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 1-3 of the present application. FIG. 14 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 1-4 of the present application. FIG. 15 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 1-5 of the present application. FIG. 16 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 1-6 of the present application. FIG. 17 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 1-7 of the present application. FIG. 18 is a diagram showing the shape of hollow silica particles according to Experimental Examples 2-1 to 2-4 according to the concentration of the water-soluble polymer electrolyte and silica precursor of the present application. FIG. 19 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 2-1 of the present application. FIG. 20 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 2-2 of the present application. FIG. 21 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 2-3 of the present application. FIG. 22 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 2-4 of the present application. FIG. 23 is a diagram showing the shape of hollow silica particles according to Experimental Examples 2-5 to 2-7 according to the concentration of the basic solution of the present application. FIG. 24 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 2-5 of the present application. FIG. 25 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 2-6 of the present application. FIG. 26 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 2-7 of the present application. Specific details for implementing the invention
[0059] Hereinafter, preferred embodiments of the present application will be described in detail with reference to the attached drawings. However, the technical concept of the present application is not limited to the embodiments described herein and may be embodied in other forms. Rather, the embodiments introduced herein are provided to ensure that the disclosed content is thorough and complete and to ensure that the concept of the present application is sufficiently conveyed to those skilled in the art.
[0060] In this specification, when a component is described as being on another component, it means that it may be formed directly on the other component or that a third component may be interposed between them. Additionally, in the drawings, the thicknesses of the films and regions are exaggerated for the effective illustration of the technical content.
[0061] Additionally, although terms such as first, second, third, etc., have been used to describe various components in the various embodiments of this specification, these components should not be limited by such terms. These terms are used merely to distinguish one component from another. Accordingly, what is referred to as the first component in one embodiment may be referred to as the second component in another embodiment. Each embodiment described and illustrated herein also includes its complementary embodiment. Furthermore, in this specification, "and / or" is used to mean including at least one of the components listed before and after it.
[0062] In the specification, singular expressions include plural expressions unless the context clearly indicates otherwise. Furthermore, terms such as "include" or "have" are intended to specify the existence of the features, numbers, steps, components, or combinations thereof described in the specification, and should not be understood as excluding the existence or addition of one or more other features, numbers, steps, components, or combinations thereof. Additionally, in this specification, "connection" is used to include both indirectly connecting multiple components and directly connecting them.
[0063] Furthermore, in describing the present application below, if it is determined that a detailed description of related known functions or configurations could unnecessarily obscure the essence of the application, such detailed description will be omitted.
[0065] FIG. 1 is a drawing for explaining a method for manufacturing hollow silica particles according to an embodiment of the present application, FIG. 2 is a drawing for explaining a method for manufacturing a core according to an embodiment of the present application, FIG. 3 is a drawing for explaining a method for manufacturing a shell according to an embodiment of the present application, FIG. 4 and FIG. 5 are drawings for explaining a shape control method according to an embodiment of the present application, and FIG. 6 is a drawing for explaining hollow silica particles according to an embodiment of the present application.
[0066] Referring to FIGS. 1 and 2, a water-soluble polymer electrolyte is dissolved in a basic atmosphere, and an aggregation source is provided to aggregate the dissolved water-soluble polymer electrolyte, thereby forming a core (1) in which the water-soluble polymer electrolyte is aggregated (S110).
[0067] Referring to FIGS. 4 and 5, the concentration of the water-soluble polymer electrolyte can be controlled in the formation of the core (1).
[0068] Accordingly, the shape of the hollow silica particles (100) formed from the core (1) can be controlled. Specifically, as the concentration of the water-soluble polymer electrolyte increases, the shape of the hollow silica particles (100) can be controlled from a spherical shape to a chain shape. More specifically, the concentration of the water-soluble polymer electrolyte can be controlled to an amount satisfying the following Equation 1.
[0069] <Equation 1>
[0070] (X - 87.5) 2 / 37.5 2 + (Y - 125) 2 / 75 2 = 1
[0071] Here, X is the concentration of the silica precursor, and Y may be the concentration of the water-soluble polymer electrolyte.
[0072] Accordingly, the hollow silica particles (100) produced from the core (1) can be controlled into a spherical shape.
[0073] Alternatively, the concentration of the above-mentioned water-soluble polymer electrolyte can be adjusted to an amount satisfying Formula 2 below.
[0074] <Equation 2>
[0075] (X - 175) 2 / 95 2 + (Y - 20) 2 / 130 2 = 1 (where X < 175, Y > 20)
[0076] Here, X is the concentration of the silica precursor, and Y may be the concentration of the water-soluble polymer electrolyte.
[0077] Accordingly, the hollow silica particles (100) produced from the core (1) can be controlled into a chain shape.
[0078] Alternatively, the concentration of the above-mentioned water-soluble polymer electrolyte can be adjusted to an amount that satisfies both Equation 1 and Equation 2.
[0079] Accordingly, the hollow silica particles (100) produced from the core (1) can be controlled into a spherical shape and a chain shape.
[0080] In other words, according to an embodiment of the present application, a mechanism for controlling the shape of the hollow silica particles (100) being manufactured can be identified. That is, according to the mechanism in which the hollow silica particles (100) are manufactured in a spherical shape when the concentration of the water-soluble polymer electrolyte satisfies Equation 1, and the hollow silica particles (100) are manufactured in a chain shape when Equation 2 is satisfied, the shape control of the hollow silica particles (100) being manufactured can be easily controlled.
[0081] According to one embodiment, as the concentration of the water-soluble polymer electrolyte increases, the particle size and pore size of the aggregated water-soluble polymer electrolyte may increase. Specifically, for example, the concentration of the water-soluble polymer electrolyte may be controlled to be greater than 48 μM and less than 176 μM. More specifically, for example, when the concentration of the water-soluble polymer electrolyte is 50 μM or more and 125 μM or less, the hollow silica particles (100) may be manufactured in a spherical shape. For another example, when the concentration of the water-soluble polymer electrolyte is 80 μM or more and 175 μM or less, the hollow silica particles (100) may be manufactured in a chain shape. The above-mentioned water-soluble polymer electrolyte may be at least one selected from the group comprising, for example, polyacrylic acid, polymethacrylic acid, polyvinyl alcohol, polyethylene glycol, polypropylene glycol, polyvinylpyrrolidone, and copolymers thereof. However, this is not limited thereto.
[0082] According to one embodiment, the water-soluble polymer electrolyte may exhibit an assembly phenomenon into a linear structure through interactions between particles due to the polarization effect of the polymer electrolyte. On the other hand, the silica precursor described later may interfere with the polarization effect while growing a shell (2) on the core (1) formed from the water-soluble polymer electrolyte. In other words, the content of the water-soluble polymer electrolyte and the silica precursor described later is controlled, and the shape of the hollow silica particles produced can be easily controlled by the combined effect resulting from the control of the content of the water-soluble polymer electrolyte and the silica precursor described later.
[0083] According to one embodiment, the weight average molecular weight of the water-soluble polymer electrolyte can be controlled to 500 g / mol or more and 500,000 g / mol or less, and preferably, to 1,000 g / mol or more and 7,000 g / mol or less for ease of dissolution during the synthesis and cleaning of the core (1) from the water-soluble polymer electrolyte. In this case, when the water-soluble polymer electrolyte having a relatively narrow molecular weight distribution is used, the core (1) having a uniform size and shape can be easily synthesized.
[0084] According to one embodiment, the aggregation source may not dissolve the water-soluble polymer electrolyte. More specifically, for example, the aggregation source may be ethanol. However, this is not limited thereto.
[0085] Accordingly, aggregation of the water-soluble polymer dissolved in the above basic atmosphere may be facilitated.
[0086] Referring further to FIGS. 1 and FIGS. 3, a silica precursor is provided in the basic atmosphere so that a shell (2) containing silica can be formed on the core (1) (S120).
[0087] Referring to FIGS. 4 and FIGS. 5, the concentration of the silica precursor can be controlled in the formation of the shell (2).
[0088] Accordingly, the shape of the hollow silica particles (100) formed from the core (1) and the shell (2) can be controlled.
[0089] In other words, according to an embodiment of the present application, the core (1) in which the water-soluble polymer electrolyte is aggregated is formed, and the silica precursor is provided to the core (1) so that the shell (2) is formed on the core (1) and an intermediate (10) can be produced before the hollow silica particle (100) is manufactured. In other words, the intermediate (10) is an intermediate formed from hollow silica particles that does not contain a hollow (3), but includes the core (1) in which the water-soluble polymer electrolyte is aggregated, and the shell (2) formed from the silica precursor on the core (1), and may include an amount satisfying Formula 1.
[0090] Accordingly, the intermediate (10) may have a spherical shape, and the hollow silica particles manufactured by removing the core 1) from the intermediate (10) may also have a spherical shape.
[0091] According to one embodiment, as the concentration of the silica precursor increases, the shape of the intermediate (10) and the hollow silica particles (100) produced from the intermediate (10) can be controlled from a chain shape to a spherical shape. More specifically, the concentration of the silica precursor can be controlled to an amount satisfying Equation 1 together with the concentration of the water-soluble polymer electrolyte described above.
[0092] Accordingly, the intermediate (10) including the core (1) and the shell (2), and the hollow silica particles (100) produced from the intermediate (10) can be controlled to have a spherical shape.
[0093] Alternatively, the concentration of the silica precursor can be adjusted to an amount satisfying Equation 2, together with the concentration of the water-soluble polymer electrolyte described above.
[0094] Accordingly, the intermediate (10) comprising the core (1) and the shell (2), and the hollow silica particles (100) produced from the intermediate (10) can be controlled in a chain shape.
[0095] Alternatively, the concentration of the silica precursor and the concentration of the water-soluble polymer electrolyte can be adjusted to an amount that satisfies both Equation 1 and Equation 2.
[0096] Accordingly, the intermediate (10) comprising the core (1) and the shell (2), and the hollow silica particles (100) produced from the intermediate (10) can be controlled into a spherical shape and a chain shape.
[0097] In other words, according to an embodiment of the present application, a mechanism for controlling the shape of the hollow silica particles (100) being manufactured can be identified. That is, according to the mechanism in which the hollow silica particles (100) are manufactured in a spherical shape when the concentration of the silica precursor satisfies Equation 1, and the hollow silica particles (100) are manufactured in a chain shape when the concentration satisfies Equation 2, the shape control of the hollow silica particles (100) being manufactured can be easily controlled.
[0098] According to one embodiment, as the concentration of the silica precursor increases, the thickness of the shell (2) formed on the core (1) may increase. Specifically, for example, the concentration of the silica precursor may be controlled to be greater than 35 mM and less than 236 mM. More specifically, for example, when the concentration of the silica precursor is 50 mM or more and 200 mM or less, the hollow silica particles (100) may be manufactured in a spherical shape. For another example, when the concentration of the silica precursor is 20 mM or more and 150 mM or less, the hollow silica particles (100) may be manufactured in a chain shape. The above silica precursor may be, for example, at least one selected from the group comprising tetraethyl orthosilicate and tetramethyl orthosilicate, or at least one selected from the group of amine group-containing silica precursors comprising 3-aminopropyl triethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl methyldiethoxysilane, 3-aminopropyl methyldimethoxysilane, and amino silane.
[0099] According to one embodiment, the water-soluble polymer electrolyte may exhibit an assembly phenomenon into a linear structure through interactions between particles due to the polarization effect of the polymer electrolyte. On the other hand, the silica precursor may hinder the polarization effect while growing a shell (2) on the core (1) formed from the water-soluble polymer electrolyte. In other words, the content of the water-soluble polymer electrolyte and the silica precursor is controlled, and the shape of the hollow silica particles produced can be easily controlled by the combined effect resulting from the control of the content of the water-soluble polymer electrolyte and the silica precursor.
[0100] According to one embodiment, the basic atmosphere may be formed from a basic solution. The basic solution may act as a catalyst for the growth of the shell (2) under the basic atmosphere. If the concentration of the basic solution is too low, the synthesis reaction of the silica precursor may be reduced, and the growth of the silica precursor may be reduced. On the other hand, if the concentration of the basic solution is too high, the synthesis reaction of the silica precursor may be accelerated, and the particles of the silica precursor may aggregate. Accordingly, the concentration of the basic solution may be adjusted to an appropriate level; specifically, for example, the concentration of the basic solution may be adjusted to greater than 0.45 M and less than or equal to 1.35 M, and preferably, the concentration may be adjusted to greater than 0.6 M and less than or equal to 1.35 M. The basic solution may be, for example, ammonia water.
[0101] Referring further to FIGS. 1 and FIGS. 6, the core (1) is removed, and a hollow silica particle (100) including the shell (1) surrounding the hollow (3) formed in the area where the core (1) was removed can be formed (S130).
[0102] According to one embodiment, the core (1) can be removed by heat treatment at a temperature above which the water-soluble polymer decomposes.
[0103] According to another embodiment, the core (1) can be removed by dissolving the water-soluble polymer in water.
[0104] As a result, the core (1) can be removed from the intermediate (10).
[0105] Accordingly, the hollow silica particle (100) having a structure including the shell (2) surrounding the hollow (3) formed in the area where the core (1) is removed can be formed.
[0107] According to the embodiments of the present application described above, the water-soluble polymer electrolyte is dissolved in the basic atmosphere, and an aggregation source is provided to aggregate the dissolved water-soluble polymer electrolyte, thereby forming the core (1) in which the water-soluble polymer electrolyte is aggregated. Additionally, the silica precursor is provided in the basic atmosphere, thereby forming the shell (2) containing silica on the core (1).
[0108] Accordingly, the intermediate (10) can be formed before being formed into the hollow silica particles (100). In other words, the intermediate (10) may include the core (1) in which the water-soluble polymer electrolyte is aggregated, and the shell (2) formed from a silica precursor on the core (1).
[0109] According to one embodiment, the intermediate (10) can be manufactured in a spherical shape when it contains an amount satisfying Formula 1.
[0110] Or, according to one embodiment, the intermediate (10) may be manufactured in a chain shape if it contains an amount satisfying Formula 2.
[0111] Or, according to one embodiment, the intermediate (10) may be manufactured in a spherical shape and a chain shape when it contains an amount satisfying both Formula 1 and Formula 2.
[0112] Furthermore, the core (1) may be removed, and the hollow silica particle (100) may be formed, comprising the shell (2) surrounding the hollow (3) formed in the area where the core (1) was removed.
[0113] According to one embodiment, the hollow silica particles (100) can be manufactured in the shape of a sphere when the intermediate (10) is manufactured in an amount satisfying Formula 1.
[0114] Alternatively, according to one embodiment, the hollow silica particles (100) may be manufactured in the chain shape when the intermediate (10) is manufactured in an amount satisfying Formula 2.
[0115] Alternatively, according to one embodiment, the hollow silica particles (100) may be manufactured in the spherical shape and the chain shape when the intermediate (10) is manufactured in an amount satisfying both Formula 1 and Formula 2.
[0116] In other words, according to an embodiment of the present application, a mechanism for controlling the shape of the intermediate (10) and the hollow silica particles (100) being manufactured can be identified. That is, according to the mechanism in which the intermediate (10) and the hollow silica particles (100) are manufactured in a spherical shape when the concentrations of the water-soluble polymer electrolyte and the silica spheres satisfy Equation 1, and the intermediate (10) and the hollow silica particles (100) are manufactured in a chain shape when Equation 2 is satisfied, the shape control of the intermediate (10) and the hollow silica particles (100) being manufactured can be easily controlled.
[0118] Specific experimental examples and characteristic evaluation results according to the embodiments of the present application are described below.
[0120] Preparation of hollow silica particles (ex 1-1) according to Experimental Example 1-1
[0121] Using a modified form of the Stober method in an ethanol solvent, an aqueous solution of 76 μM polyacrylic acid (PAA) with a weight-average molecular weight of 3,000–5,000 g / mol was dissolved in 0.90 M ammonia water.
[0122] Subsequently, the solution in which the polyacrylic acid was dissolved was mixed with 60 mL of ethanol, and while stirring the mixed solution at room temperature, 138 mM of tetraethyl orthosilicate (TEOS) was added in five portions at 1-hour intervals.
[0123] Afterwards, the reaction was carried out at room temperature for 10 hours, and after the reaction was finished, the particles were washed with water using a centrifuge to produce hollow silica particles (ex 1-1) according to Experimental Example 1-1.
[0125] Preparation of hollow silica particles (ex 1-2) according to Experimental Example 1-2
[0126] In the above-described Experimental Example 1-1, a 95 μM aqueous solution of polyacrylic acid (PAA) was added to 0.90 M ammonia water, and 138 mM tetraethyl orthosilicate (TEOS) was added to prepare hollow silica particles (ex 1-2) according to Experimental Example 1-2.
[0128] Preparation of hollow silica particles (ex 1-3) according to Experimental Example 1-3
[0129] In the above-described Experimental Example 1-1, a 77 μM aqueous solution of polyacrylic acid (PAA) was added to 0.90 M ammonia water, and 104 mM tetraethyl orthosilicate (TEOS) was added to prepare hollow silica particles (ex 1-3) according to Experimental Example 1-3.
[0131] Preparation of hollow silica particles (ex 1-4) according to Experimental Example 1-4
[0132] In the above-described Experimental Example 1-1, a 96 μM aqueous solution of polyacrylic acid (PAA) was added to 0.90 M ammonia water, and 104 mM tetraethyl orthosilicate (TEOS) was added to prepare hollow silica particles (ex 1-4) according to Experimental Example 1-4.
[0134] Preparation of hollow silica particles (ex 1-5) according to Experimental Example 1-5
[0135] In the above-described Experimental Example 1-1, a 58 μM aqueous solution of polyacrylic acid (PAA) was added to 0.90 M ammonia water, and 104 mM tetraethyl orthosilicate (TEOS) was added to prepare hollow silica particles (ex 1-5) according to Experimental Example 1-5.
[0137] Preparation of hollow silica particles (ex 1-6) according to Experimental Example 1-6
[0138] In the above-described Experimental Example 1-1, a 97 μM aqueous solution of polyacrylic acid (PAA) was added to 0.90 M ammonia water, and 53 mM tetraethyl orthosilicate (TEOS) was added to prepare hollow silica particles (ex 1-6) according to Experimental Example 1-6.
[0140] Preparation of hollow silica particles (ex 1-7) according to Experimental Example 1-7
[0141] In the above-described Experimental Example 1-1, 117 μM of an aqueous polyacrylic acid (PAA) solution was added to 0.90 M of ammonia water, and 35 mM of tetraethyl orthosilicate (TEOS) was added to prepare hollow silica particles (ex 1-7) according to Experimental Example 1-7.
[0143] Preparation of hollow silica particles (ex 2-1) according to Experimental Example 2-1
[0144] In the above-described Experimental Example 1-1, a 19 μM aqueous solution of polyacrylic acid (PAA) was added to 0.90 M ammonia water, and 236 mM tetraethyl orthosilicate (TEOS) was added to prepare hollow silica particles (ex 2-1) according to Experimental Example 2-1.
[0146] Preparation of hollow silica particles (ex 2-2) according to Experimental Example 2-2
[0147] In the above-described Experimental Example 1-1, 113 μM of an aqueous solution of polyacrylic acid (PAA) was added to 0.90 M of ammonia water, and 204 mM of tetraethyl orthosilicate (TEOS) was added to prepare hollow silica particles (ex 2-2) according to Experimental Example 2-2.
[0149] Preparation of hollow silica particles (ex 2-3) according to Experimental Example 2-3
[0150] In the above-described Experimental Example 1-1, a 48 μM aqueous solution of polyacrylic acid (PAA) was added to 0.90 M ammonia water, and 79 mM tetraethyl orthosilicate (TEOS) was added to prepare hollow silica particles (ex 2-3) according to Experimental Example 2-3.
[0152] Preparation of hollow silica particles (ex 2-4) according to Experimental Example 2-4
[0153] In the above-described Experimental Example 1-1, 176 μM of an aqueous polyacrylic acid (PAA) solution was added to 0.90 M of ammonia water, and 35 mM of tetraethyl orthosilicate (TEOS) was added to prepare hollow silica particles (ex 2-4) according to Experimental Example 2-4.
[0155] Preparation of hollow silica particles (ex 2-5) according to Experimental Example 2-5
[0156] In the above-described Experimental Example 1-1, a 77 μM aqueous solution of polyacrylic acid (PAA) was added to 0.45 M ammonia water, and 104 mM tetraethyl orthosilicate (TEOS) was added to prepare hollow silica particles (ex 2-5) according to Experimental Example 2-5.
[0158] Preparation of hollow silica particles (ex 2-6) according to Experimental Example 2-6
[0159] In the above-described Experimental Example 1-1, a 77 μM aqueous solution of polyacrylic acid (PAA) was added to 0.90 M ammonia water, and 104 mM tetraethyl orthosilicate (TEOS) was added to prepare hollow silica particles (ex 2-6) according to Experimental Example 2-6.
[0161] Preparation of hollow silica particles (ex 2-7) according to Experimental Example 2-7
[0162] In the above-described Experimental Example 1-1, a 77 μM aqueous solution of polyacrylic acid (PAA) was added to 1.35 M ammonia water, and 104 mM tetraethyl orthosilicate (TEOS) was added to prepare hollow silica particles (ex 2-7) according to Experimental Example 2-7.
[0164] Experimental Examples 1-1 to 2-7 described above can be summarized as shown in Table 1 below.
[0165] division Water-soluble polymer electrolyte (PAA) concentration (μM) Silica precursor (TEOS) concentration (mM) Basic solution (ammonia water) concentration (M) Experiment Example 1-1 (ex 1-1) 76 138 0.90 Experiment Example 1-2 (ex 1-2) 95 138 0.90 Experiment Example 1-3 (ex 1-3) 77 104 0.90 Experiment Example 1-4 (ex 1-4) 96 104 0.90 Experiment Example 1-5 (ex 1-5) 58 104 0.90 Experiment Example 1-6 (ex 1-6) 97 53 0.90 Experiment Example 1-7 (ex 1-7) 117 35 0.90 Experiment Example 2-1 (ex 2-1) 19 236 0.90 Experiment Example 2-2 (ex 2-2) 113 204 0.90 Experiment Example 2-3 (ex 2-3) 48 79 0.90 Experiment Example 2-4 (ex 2-4) 176 35 0.90 Experiment Example 2-5 (ex 2-5) 77 104 0.45 Experiment Example 2-6 (ex 2-6) 77 104 0.90 Experiment Example 2-7 (ex 2-7) 77 104 1.35
[0167] FIG. 7 is a transmission electron microscope (TEM) image after 5 hours have elapsed since providing a silica precursor in the hollow silica particle manufacturing process according to Experimental Example 1-3 of the present application, FIG. 8 is a transmission electron microscope (TEM) image after 15 hours have elapsed since providing a silica precursor in the hollow silica particle manufacturing process according to Experimental Example 1-3 of the present application, and FIG. 9 is a transmission electron microscope (TEM) image after washing the intermediate prepared according to the hollow silica particle manufacturing process according to Experimental Example 1-3 of the present application.
[0168] Referring to FIGS. 7 to 9, it can be seen that the diameter of the hollow silica particle (100) is 20 nm or more to 200 nm or less, and the thickness of the shell (2) is 3 nm or more to 90 nm or less.
[0169] According to the embodiments and experimental examples of the present application, the above-described hollow silica particle (100) manufacturing process can be performed at room temperature. The intermediate (10) may be cleaned using water, with centrifugation or a filter. Alternatively, the intermediate (10) may be calcined at a temperature, for example, 500°C or higher, at which the water-soluble polymer electrolyte, for example, polyacrylic acid (PAA), decomposes.
[0170] According to the embodiments and experimental examples of the present application, the concentrations of the water-soluble polymer electrolyte, the silica precursor, and the basic solution in ethanol may be major factors determining the size and shape of the hollow silica particles (100). More specifically, the amount, concentration, and molecular weight of the water-soluble polymer electrolyte may determine the pore size of the hollow silica particles (100). Additionally, the amount and concentration of the silica precursor may determine the shell thickness and shape of the hollow silica particles (100). Furthermore, the basic solution may determine the pore size, shell thickness, and particle shape of the hollow silica particles (100) as a catalyst. Additionally, the ethanol may serve as a dispersion medium for nanoparticles, and the amount of ethanol may determine the final concentration of other reagents within the ethanol.
[0172] FIG. 10 is a diagram showing the shape of hollow silica particles according to Experimental Examples 1-1 to 1-7 according to the concentration of the water-soluble polymer electrolyte and silica precursor of the present application; FIG. 11 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 1-1 of the present application; FIG. 12 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 1-2 of the present application; FIG. 13 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 1-3 of the present application; FIG. 14 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 1-4 of the present application; FIG. 15 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 1-5 of the present application; FIG. 16 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 1-6 of the present application; FIG. 17 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 1-7 of the present application.
[0173] Referring to Fig. 10 and Table 1 above, in Experimental Examples 1-1 to 1-7, the concentration of the basic solution, i.e., ammonia water, was kept the same at 0.90 M.
[0174] In FIG. 10, the region containing O represents a region where the hollow silica particles (100) have a spherical shape, the region containing Δ represents a region where the hollow silica particles (100) have a chain shape, and the region containing □ represents a region where the hollow silica particles (100) have both a spherical shape and a chain shape.
[0175] Referring to FIGS. 10 to 17, it can be seen that the hollow silica particles (ex 1-1 to ex 1-5) according to Experimental Examples 1-1 to 1-5 have a spherical shape, the hollow silica particles (ex 1-7) according to Experimental Example 1-7 have a chain shape, and the hollow silica particles (ex 1-6) according to Experimental Example 1-6 have both a spherical shape and a chain shape.
[0176] Referring to FIGS. 10 to 14, it can be seen that in the hollow silica particles (ex 1-1 to ex 1-4) according to Experimental Examples 1-1 to 1-4, the higher the concentration of the water-soluble polymer electrolyte, the larger the pore size, and the higher the concentration of the silica precursor, the thicker the shell. In addition, as with the hollow silica particles (ex 1-2, ex 1-3) according to Experimental Examples 1-2 and 1-3, when the ratio of the concentration of the silica precursor to the concentration of the water-soluble polymer electrolyte is similar, the overall shape is similar but there is a difference in particle size. More specifically, it can be seen that the size of the hollow silica particles (ex 1-2) according to Experimental Example 1-2, which have higher concentrations of the water-soluble polymer electrolyte and the silica precursor than those of Experimental Example 1-3 (ex 1-3), is larger.
[0177] Referring to FIGS. 10 and FIGS. 15 to 17, it can be seen that the hollow silica particles according to Experimental Example 1-5 (ex 1-5) have a spherical shape with a small pore size and a thick shell because the concentration of the water-soluble polymer electrolyte is low and the concentration of the silica precursor is high. On the other hand, the hollow silica particles according to Experimental Example 1-7 (ex 1-7) have a chain shape with a large pore size and a thick shell because the concentration of the water-soluble polymer electrolyte is high and the concentration of the silica precursor is low. In addition, the hollow silica particles according to Experimental Example 1-6 (ex 1-6) have both a spherical shape and a chain shape because they are synthesized under conditions corresponding to the intermediate region of the synthesis conditions of Experimental Example 1-5 and Experimental Example 1-7.
[0178] The above-mentioned water-soluble polymer electrolyte may exhibit an assembly phenomenon into a linear structure through interactions between particles due to the polarization effect of the polymer electrolyte. In this process, the shell (2) formed from the silica precursor may act as a factor that hinders the polarization effect. Accordingly, outside the uniform formation region of the hollow silica particle (100), as the proportion of the shell (2) within the hollow silica particle (100) decreases, the hollow silica particle (100) may have a tendency to form in a chain shape. In addition, in other cases, the hollow silica particle (100) may have an aggregated lump shape.
[0180] FIG. 18 is a diagram showing the shape of hollow silica particles according to Experimental Examples 2-1 to 2-4 according to the concentration of the water-soluble polymer electrolyte and silica precursor of the present application, FIG. 19 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 2-1 of the present application, FIG. 20 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 2-2 of the present application, FIG. 21 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 2-3 of the present application, and FIG. 22 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 2-4 of the present application.
[0181] Referring to FIG. 18 and Table 1 above, in Experimental Examples 2-1 to 2-4, the concentration of the basic solution, i.e., ammonia water, was kept the same at 0.90 M.
[0182] In FIG. 18, the region containing O represents a region where the hollow silica particles (100) have a spherical shape, the region containing Δ in FIG. 18 represents a region where the hollow silica particles (100) have a chain shape, the region containing □ in FIG. 18 represents a region where the hollow silica particles (100) have both a spherical shape and a chain shape, and the region containing X in FIG. 18 represents a region where the hollow silica particles (100) have a lump shape.
[0183] Referring to FIGS. 18 to 22, the hollow silica particles (ex 2-1 to ex 2-4) according to Experimental Examples 2-1 to 2-4 can be observed to be aggregated into a lump shape or broken (br). More specifically, in Experimental Examples 2-1 to 2-4 (ex 2-1 to ex 2-4), when the concentration of the water-soluble polymer electrolyte and / or the silica precursor is higher than in Experimental Examples 1-1 to 1-7 (ex 1-1 to ex 1-7), it can be observed that they are aggregated into a lump shape. On the other hand, in Experimental Examples 2-1 to 2-4 (ex 2-1 to ex 2-4), when the concentration of the water-soluble polymer electrolyte and / or the silica precursor is lower than in Experimental Examples 1-1 to 1-7 (ex 1-1 to ex 1-7), a broken shape (br) can be observed.
[0185] FIG. 23 is a diagram showing the shape of hollow silica particles according to Experimental Examples 2-5 to 2-7 according to the concentration of the basic solution of the present application, FIG. 24 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 2-5 of the present application, FIG. 25 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 2-6 of the present application, and FIG. 26 is a transmission electron microscope (TEM) image of hollow silica particles according to Experimental Example 2-7 of the present application.
[0186] Referring to FIG. 23 and Table 1 above, in Experimental Examples 2-5 to 2-7, the concentrations of the water-soluble polymer electrolyte and the silica precursor were set to be the same at 77 μM and 104 mM, respectively.
[0187] Referring to FIGS. 23 to 26, it can be seen that when the concentration of the basic solution is 0.90 M, i.e., in the case of the hollow silica particles according to Experimental Example 2-6 (ex 2-6), they have a uniform spherical shape. On the other hand, when the concentration of the basic solution is 0.45 M, i.e., in the case of the hollow silica particles according to Experimental Example 2-5 (ex 2-5), they have particles with a thin shell (2) and a net-like silica mass shape. In addition, when the concentration of the basic solution is 1.35 M, i.e., in the case of the hollow silica particles according to Experimental Example 2-7 (ex 2-7), they have a mass shape.
[0188] Through FIGS. 23 to 26, it can be seen that when the concentration of the basic solution is low, the water-soluble polymer electrolyte is weakly aminated, and a weak electrostatic attraction is formed. On the other hand, when the concentration of the basic solution is high, the hydrolysis and dehydration condensation rates of the silica precursor become excessively fast, and aggregation occurs between particles due to the rapid reaction rate. Meanwhile, overall, it can be seen that the pore size of the hollow silica particles (100) decreases as the concentration of the basic solution increases. This may be because the charge of the chain increases as the degree of amination of the carboxyl groups present in the chain of the water-soluble polymer electrolyte increases, and as a result, the electrical repulsion is strengthened.
[0189] Thus, it can be seen that the concentration of the basic solution must be appropriately controlled in order to form the hollow silica particles (100) of a uniform shape.
[0191] Although the present application has been described in detail using preferred embodiments, the scope of the present application is not limited to specific embodiments and should be interpreted by the appended claims. Furthermore, those skilled in the art will understand that many modifications and variations are possible without departing from the scope of the present application. Explanation of the symbols
[0193] 1: Core 2: Shell 3: Communist China 10: Intermediate 100: Hollow silica particles
Claims
Claim 1 A method for manufacturing hollow silica particles, comprising: a step of dissolving a water-soluble polymer electrolyte in a basic atmosphere and providing an aggregation source to aggregate the dissolved water-soluble polymer electrolyte, thereby forming a core in which the water-soluble polymer electrolyte is aggregated; a step of providing a silica precursor in the basic atmosphere to form a shell containing silica on the core; and a step of removing the core and forming hollow silica particles including the shell surrounding a hollow formed in the region where the core was removed, wherein the step of forming the core controls a linear assembly structure by the polarization effect of the polymer electrolyte by controlling the concentration of the water-soluble polymer electrolyte, and the step of forming the shell controls the growth rate of the silica shell on the core by controlling the concentration of the silica precursor, thereby controlling the shape of the finally manufactured hollow silica particles to a spherical shape or a chain shape. Claim 2 A method for manufacturing hollow silica particles according to claim 1, wherein as the concentration of the silica precursor increases, the shape of the hollow silica particles is controlled from a chain shape to a spherical shape. Claim 3 A method for manufacturing hollow silica particles according to claim 1, wherein as the concentration of the water-soluble polymer electrolyte increases, the shape of the hollow silica particles is controlled from a spherical shape to a chain shape. Claim 4 A method for manufacturing hollow silica particles according to claim 1, wherein as the concentration of the water-soluble polymer electrolyte increases, the particle size and pore size of the aggregated water-soluble polymer electrolyte increase, and as the concentration of the silica precursor increases, the thickness of the shell formed on the core increases. Claim 5 A method for manufacturing hollow silica particles according to claim 1, wherein the core is removed by heat treatment at a temperature above which the water-soluble polymer decomposes, or the water-soluble polymer is removed by dissolving in water. Claim 6 A method for manufacturing hollow silica particles according to claim 1, wherein the basic atmosphere is formed from a basic solution, and the basic solution acts as a catalyst for the growth of the shell under the basic atmosphere, wherein the concentration is controlled to be greater than 0.45 M and less than or equal to 1.35 M, and comprises ammonia water. Claim 7 A method for producing hollow silica particles according to claim 1, wherein the aggregation source does not dissolve the water-soluble polymer electrolyte and contains ethanol. Claim 8 In claim 1, the silica precursor comprises having a concentration controlled to be greater than 35 mM and less than 236 mM, and comprises at least one selected from the group comprising tetraethyl orthosilicate and tetramethyl orthosilicate, or at least one selected from the group comprising amine group-containing silica precursors comprising 3-aminopropyl triethoxysilane, 3-aminopropyl trimethoxysilane, 3-aminopropyl methyldiethoxysilane, 3-aminopropyl methyldimethoxysilane, and amino silane, and the water-soluble polymer electrolyte comprises having a concentration controlled to be greater than 48 μM and less than 176 μM, and polyacrylic acid, A method for manufacturing hollow silica particles comprising at least one selected from the group comprising polymethacrylic acid, polyvinyl alcohol, polyethylene glycol, polypropylene glycol, polyvinylpyrrolidone, and copolymers thereof. Claim 9 A method for controlling the shape of hollow silica particles, comprising: a step of manufacturing a core aggregated with a water-soluble polymer electrolyte; and a step of providing a silica precursor to the core to form a shell on the core, wherein the hollow silica particles are controlled to a spherical shape by controlling the content to satisfy the following Formula 1. <Formula 1> (X - 87.5) 2 / 37.5 2 + (Y - 125) 2 / 75 2 = 1(where X is the concentration of the silica precursor and Y is the concentration of the water-soluble polymer electrolyte) Claim 10 A method for controlling the shape of hollow silica particles, comprising: a step of manufacturing a core aggregated with a water-soluble polymer electrolyte; and a step of providing a silica precursor to the core to form a shell on the core, wherein the hollow silica particles are controlled into a chain shape by controlling the content to satisfy the following Equation 2. <Equation 2> (X - 175) 2 / 95 2 + (Y - 20) 2 / 130 2 = 1 (where X < 175, Y > 20) (where X is the concentration of the silica precursor and Y is the concentration of the water-soluble polymer electrolyte) Claim 11 A method for controlling the shape of hollow silica particles according to claim 9 or 10, comprising controlling the hollow silica particles into a spherical shape and a chain shape by controlling the content to satisfy both Formula 1 and Formula 2. Claim 12 An intermediate formed of hollow silica particles, comprising: a core aggregated with a water-soluble polymer electrolyte; and a shell formed of a silica precursor on the core, wherein the shell comprises an amount satisfying Formula 1 below and has a spherical shape. <Formula 1> (X - 87.5) 2 / 37.5 2 + (Y - 125) 2 / 75 2 = 1(where X is the concentration of the silica precursor and Y is the concentration of the water-soluble polymer electrolyte) Claim 13 An intermediate formed of hollow silica particles, comprising: a core aggregated with a water-soluble polymer electrolyte; and a shell formed of a silica precursor on the core, wherein the shell comprises an amount satisfying the following Formula 2 and has a chain shape. <Formula 2> (X - 175) 2 / 95 2 + (Y - 20) 2 / 130 2 = 1 (where X < 175, Y > 20) (where X is the concentration of the silica precursor and Y is the concentration of the water-soluble polymer electrolyte) Claim 14 An intermediate of hollow silica particles according to claim 12 or 13, comprising an amount satisfying both Formula 1 and Formula 2, and having a spherical shape and a chain shape.
Citation Information
Patent Citations
Hollow silicone particles and preparation methods thereof
KR101888296B1
Method for Preparing Hollow Silica Particle
KR1020120056337A
Method of producing Silica Nanostructure
KR1020160134361A